calculus

posted by .

Find
lim as (x,y) goes to (0,0) of
(e^(-x^2-y^2)-1)/(x^2+y^2).

  • calculus -

    lim (e^-u^2-1)/u^2
    = lim (-2u e^-u^2)/2u = -1

    Now let u^2 = x^2+y^2

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Calculus

    How do I solve lim(x-->pi/4)(sinx-cosx)/cos(2x) The (x-->pi/4) goes below the lim. Should i just substitute the x's with pi/4?
  2. Calculus B

    Find lim as x goes to 0 of (xsinx)/(1-cosx)
  3. calculus

    f(x)= 3x+2, x<0 3, x=0 x^2+1, x>0 g(x)= -x+3, x<1 0, x=1 x^2, x>1 find a) lim x->0+ g(f(x)) b)lim x->0- g(f(x)) c) lim x->1+ f(g(x)) d)lim x->1- f(g(x)) I am trying to understand these. Help appreciated. Have …
  4. Calculus

    Find the indicated limits. If the limit does not exist, so state, or use the symbol + ∞ or - ∞. f(x) = { 2 - x if x ≤ 3 { -1 + 3x - x^2 if x > 3 a) lim 3+ f(x) x->3 b) lim 3- f(x) x->3 c) lim f(x) x->3 …
  5. Calculus

    Find the indicated limits. If the limit does not exist, so state, or use the symbol + ∞ or - ∞. f(x) = { 2 - x if x ≤ 3 { -1 + 3x - x^2 if x > 3 a) lim 3+ f(x) x->3 b) lim 3- f(x) x->3 c) lim f(x) x->3 …
  6. Calculus

    Find the following limits algebraically or explain why they don’t exist. lim x->0 sin5x/2x lim x->0 1-cosx/x lim x->7 |x-7|/x-7 lim x->7 (/x+2)-3/x-7 lim h->0 (2+h)^3-8/h lim t->0 1/t - 1/t^2+t
  7. Calculus

    Find the limit. lim 5-x/(x^2-25) x-->5 Here is the work I have so far: lim 5-x/(x^2-25) = lim 5-x/(x-5)(x+5) x-->5 x-->5 lim (1/x+5) = lim 1/10 x-->5 x-->5 I just wanted to double check with someone and see if the answer …
  8. calculus1

    find limit if it existed 1)lim x goes to 0 tanx/2x^2-8x 2)lim x goes to-2 x^3+8/x^4-16
  9. calculus1

    Find limit if exists 1. Lim x goes to 0 x^2cos(1/x^3) 2.lim x goes to 1 to the left 4x/x^2+2x-3 3. Lim x goes to π to the right cscx
  10. Math - Calculus

    f(x) = { x^2sin(1/x), if x =/= 0 0, if x=0} a. find lim(x->0)f(x) and show that f(x) is continuous at x=0. b, find f'(0) using the definition of the derivative at x=0: f'(x)=lim(x->0) (f(x)-f(0)/x) c. Show that lim(x->0)f'(x) …

More Similar Questions